Linking the balanced scorecard to sustainability: An empirical study of local government companies - Hardani, Rano; Setyadi, Djoko; Mintarti, Sri; Abidin, Zainal; Yudaruddin, Rizky (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to analyze how the four perspectives of the Balanced Scorecard (BSC) financial, customer, internal business processes, and learning and growth affect organizational performance and sustainable development in Local Government Companies (LGCs). It also examines the mediating role of organizational performance in achieving sustainability outcomes. A quantitative, cross-sectional survey was conducted among 150 middle and top management officials from seven LGCs in East Kalimantan, Indonesia. Census sampling was employed, and t-test analysis was used to test nine hypotheses derived from theoretical and empirical frameworks. The findings reveal that the customer and learning and growth perspectives significantly enhance organizational performance, while the financial and internal business perspectives do not. In terms of sustainable development, only the financial perspective shows a significant positive effect. Surprisingly, the customer perspective negatively influences sustainability, whereas the internal business and learning and growth perspectives have no significant impact. Organizational performance itself does not significantly contribute to sustainability outcomes. The study concludes that financial strength facilitates sustainability investments, while a strong customer focus may potentially hinder long-term sustainability goals. Aligning BSC implementation with a broader sustainability vision is essential for LGCs to generate enduring value. The results underscore the need for LGCs to integrate sustainability considerations into strategic management practices. Public managers should ensure that BSC frameworks are adapted to reflect sustainability objectives beyond conventional performance measures.